RETRACTED: ECT2 Increases the stability of EGFR and Tumorigenicity by Inhibiting Grb2 Ubiquitination in Pancreatic Cancer - Wang, Junxiong; Yang, Shuo; Min, Li; Zhu, Shengtao; Guo, Shuilong; Zhang, Shutian (Frontiers in Oncology, 2021)
The poor prognosis of patients with pancreatic ductal adenocarcinoma (PDAC) is associated with the invasion and metastasis of tumor cells. Epithelial cell transforming 2 (ECT2) is a guanine nucleotide exchange factor (GEF) of the Rho family of GTPases. It has also been reported that upregulation of ECT2 in pancreatic cancer, but the role and mechanism of ECT2 have not been previously determined. We found that ECT2 was significantly elevated in PDAC tissues and cells, correlated with more advanced AJCC stage, distant metastases, and overall survival of patients with PDAC. Inhibition and overexpression tests showed that ECT2 promoted proliferation, migration and invasion in vitro, and promoted tumor growth and metastasis in vivo. We determined that ECT2 was involved in the post-translational regulation of Grb2. ECT2 inhibited the degradation of Grb2 through deubiquitination. Furthermore, knockdown of ECT2 downregulated EGFR levels by accelerating EGFR degradation. EGF stimulation facilitated the formation of ECT2-Grb2 complex. Overall, our findings indicated that ECT2 could be used as a promising new therapeutic candidate for PDAC.